Noble evaporative battery thermal management system for EV/HEV - Rahman, Mohammed Ataur; Ahmed, Helmi; Hawlader, Mohammad Nurul Alam (2014)

(untitled)
Electrical car battery voltage changes significantly to meet the power demands while the car is in acceleration. Battery pack needs to generate a high output within a very short time to meet the power demand of the car at the time of momentary peak load. These peak load periods generate powerful electrical currents, causing significant warming of the Li-ion cells due to internal resistance causes internal cells damage. LiFePO4 batteries, however, can be used efficiently only within a desired operating temperature in the range 20ºC - 40ºC. The battery operating temperature of 40ºC and above, the battery life span is reduced. The rationale of this study is to develop an innovative evaporative battery cooling thermal management system (EC-BThMS) to control the battery temperature in the range of 20ºC - 40ºC in order to increase the battery life span and to improve the battery performance. The proposed thermal management system has been developed by developing the evaporative system with estimating the total cooling loads and thermal behavior of the cells of battery. The developed thermal management system has made the battery temperature in the range of 20ºC - 40ºC during discharging process. The experiment on EC-BThMS was conducted both in IIUM and Sepang F1 international circuit. The experimental result of prototype EC-BThMS in SepangF1 has been compared with air cooling battery thermal management systems (AC-BThMS) by using PROTON Saga car. It is found that the PROTON saga car with EC-BThMS can save 17.69% more energy than with AC-BThM 1 and 23% than with AC-BThMS 2. As compared with these two other test cars equipped with cooled air as the medium of cooling for the battery pack, it is observed that the developed cooling system for our EV is more efficient in terms of travelling distance and time, and also more energy efficiency. The correlations between the measured and predicted values of temperature profiles of the battery during operation have been found to be 97.3%. This is indicates that the predicted data over the measured data have a closed agreement and thus, substantially verified the mathematical model.